Assessment of health-related quality of life in children with cancer using PedsQL™ (a preliminary study) - lvony Yuyu Susanto; Soedjatmiko Soedjatmiko; Sukman Tulus Putra (Indonesian Pediatric Society, 2009)
Background Cancer in children can adversely affect theirdevelopments and growth. The assessment of health-relatedquality of life (HRQL) will justifY its physical and psychologicaleffects.Methods Seventy-seven subjects who underwent therapy wereassessed using the PedsQL™, which consisted of parent-proxyreports and or child-self reports. PedsQL™ is assessments ofphysical, social, emotional and role functions. The controlgroup was students with the same number and age as the sample group.Results Children with cancer had lower HRQL than normalhealthy children (odds ratio 3. 7). Children with cancer who camefrom low socio-economic families had lower social functions andgirls had tendencies to have lower quality oflife. Fathers' education had strong influence in children's quality of life. Leukemic patients had better quality of life than those of lymphoma and solid organ tumor. Group with age of diagnosis at 6-9 year old had lower HRQL compared with younger or older groups. The longer period of illness was, the more emotional function would improved. Despite of a good accordance between parents' and child's reports, parents usually had reports about having lower quality of life.Conclusions Children's HRQL is influenced by clinicalcharacteristics and social-demographic variables differently.Assessment of the children's HRQL is better done with parentsand or child as the source of information.